Lung adenocarcinoma with bladder metastasis: A case report and literature review - Liu, Yuying; Dong, Xinyue; Li, Tao; Xing, Yanke; Liu, Na (Frontiers in Oncology, 2023)
Background: Lung cancer is the most common cause of cancer-related mortality in the world. Unfortunately, more than 50% of patients have already metastasized at the time of diagnosis, contributing to morbidity and mortality. Common sites of metastasis are adrenal glands, liver, bone, and brain. Bladder metastasis is rare and should prompt a careful differential consideration of primary bladder cancer. Case description: Here, we report a 72-year-old female who went to the hospital for "gross hematuria for one day". Cystoscopy showed space-occupying lesions in the bladder. During the general CT examination, space-occupying lesions in the lower lobe of the lung were found. Peripheral lung cancer with multiple lymph node metastases, pulmonary metastasis, and left pleural effusion were considered. Transurethral cystoscopic resection of the bladder tumor and pleural effusion cell block examination were performed to clarify the diagnosis. Combined with morphological and immunohistochemical results, both pathological results supported a diagnosis of lung adenocarcinoma metastasis, and gene detection was carried out. EGFR, ALK, and ROS-1 were negative. According to the genetic testing results, there was no corresponding targeted drug, so we administered chemotherapy, and one-year survival was achieved, which was better than expected based on other studies. Conclusion: This paper describes a case of lung adenocarcinoma metastatic to the bladder and includes a review of the literature to provide clinicians with diagnostic and treatment experience and help avoid misdiagnosis and mistreatment.